Pseudorhabdosynochus species (Monogenoidea, Diplectanidae) parasitizing groupers (Serranidae, Epinephelinae, Epinephelini) in the western Atlantic Ocean and adjacent waters, with descriptions of 13 new species - Kritsky Delane C.; Bakenhaster Micah D.; Adams Douglas H. (Parasite, 2015)
Seventeen of twenty-three species of groupers collected from the western Atlantic Ocean and adjacent waters were infected with 19 identified species (13 new) of Pseudorhabdosynochus Yamaguti, 1958 (Dactylogyridea, Diplectanidae); specimens of the Spanish flag Gonioplectrus hispanus, coney Cephalopholis fulva, marbled grouper Dermatolepis inermis, mutton hamlet Alphestes afer, and misty grouper Hyporthodus mystacinus were not infected; the yellowmouth grouper Mycteroperca interstitialis and yellowfin grouper Mycteroperca venenosa were infected with unidentified species of Pseudorhabdosynochus; the Atlantic creolefish Paranthias furcifer was infected with an unidentified species of Diplectanidae that could not be accommodated in Pseudorhabdosynochus. The following species of Pseudorhabdosynochus are described or redescribed based entirely or in part on new collections: Pseudorhabdosynochus americanus (Price, 1937) Kritsky & Beverley-Burton, 1986 from Atlantic goliath grouper Epinephelus itajara; Pseudorhabdosynochus yucatanensis Vidal-Martínez, Aguirre-Macedo & Mendoza-Franco, 1997 and Pseudorhabdosynochus justinella n. sp. from red grouper Epinephelus morio; Pseudorhabdosynochus kritskyi Dyer, Williams & Bunkley-Williams, 1995 from gag Mycteroperca microlepis; Pseudorhabdosynochus capurroi Vidal-Martínez & Mendoza-Franco, 1998 from black grouper Mycteroperca bonaci; Pseudorhabdosynochus hyphessometochus n. sp. from Mycteroperca interstitialis; Pseudorhabdosynochus sulamericanus Santos, Buchmann & Gibson, 2000 from snowy grouper Hyporthodus niveatus and Warsaw grouper Hyporthodus nigritus (new host record); Pseudorhabdosynochus firmicoleatus n. sp. from yellowedge grouper Hyporthodus flavolimbatus and snowy grouper H. niveatus; Pseudorhabdosynochus mcmichaeli n. sp., Pseudorhabdosynochus contubernalis n. sp., and Pseudorhabdosynochus vascellum n. sp. from scamp Mycteroperca phenax; Pseudorhabdosynochus meganmarieae n. sp. from graysby Cephalopholis cruentata; Pseudorhabdosynochus beverleyburtonae (Oliver, 1984) Kritsky & Beverley-Burton, 1986 from dusky grouper Mycteroperca marginata; Pseudorhabdosynochus mizellei n. sp. from red hind Epinephelus guttatus; Pseudorhabdosynochus williamsi n. sp. from rock hind Epinephelus adscensionis; Pseudorhabdosynochus bunkleywilliamsae n. sp. from Nassau grouper Epinephelus striatus; Pseudorhabdosynochus mycteropercae n. sp. from tiger grouper Mycteroperca tigris; and Pseudorhabdosynochus tumeovagina n. sp. from speckled hind Epinephelus drummondhayi. Pseudorhabdosynochus woodi n. sp. from red hind Epinephelus guttatus is described based on specimens from the US National Parasite Collection (USNPC). Drawings of the haptoral and copulatory sclerites of the type specimens in the USNPC of Pseudorhabdosynochus monaensis Dyer, Williams & Bunkley-Williams, 1994 from rock hind Epinephelus adscensionis are presented. Finally, a note confirming Pseudorhabdosynochus epinepheli Yamaguti, 1958 rather than its senior synonym Pseudorhabdosynochus epinepheli (Yamaguti, 1938) Kritsky & Beverley-Burton, 1986 as the type species of Pseudorhabdosynochus is provided.